"Narrating Vietnamese history is the best way to open a can of worms…": in conversation with Marcelino Truong. Issue 3 (4th May 2022) - Gusain, Abhilasha; Jha, Smita
ABSTRACT: In this interview, Marcelino Truong discusses his take on the Vietnam War history as portrayed in his two graphic narratives, Such A Lovely Little War and Saigon Calling: London 1963–75 . Truong's life experiences, memories, and personal narration work against the notions of forgetting, invisibility, and negation that often underlie the official discourse. In his works, the 'autobiographical' and the 'personal' puts the 'official' under scrutiny. Graphic narratives posit a challenge to the culture of invisibility and provide dynamism to the idea of history and memory by recording and materializing them. As Truong points out in Saigon Calling, 'these days, "no photos" means "it doesn't exist"', it is precisely against this negation that his graphic narratives stand out and delineate facts as well as personal accounts which otherwise find no records ( Saigon Calling 274). He reflects upon ideas like the narration of historical events, propaganda, 'war of images', and highlights some of the research that went into creating these works.